Pengetahuan Tentang Talasemia pada Mahasiswa Kedokteran dan Dokter Umum di Bandung serta Prevalensi Karir β-Thalassemia - Sahiratmadja, Edhyana; Wijaya, Michelle Angelica; Widjajakusuma, Anggraini; Maskoen, Ani Melani; Dewantoro, Julius Broto; Panigoro, Ramdan (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2020)
Background: Thalassemia major ranks 5th among catastrophic diseases according to the National Health Insurance, BPJS. Health workers are expected to have good knowledge about thalassemia to raise public awareness for thalassemia carrier early detection. Aim: To explore the knowledge about thalassemia among medical students and general practitioners (GPs) in Bandung, and the prevalence of β-thalassemia carrier.Methods: Analytic study was designed using questionnaire to compare knowledge. The prevalence of anemia due to iron deficiency or β-thalassemia carrier was described using Mentzer Index (MCV/RBC) and Shine and Lal index (MCV*MCV*MCH/100). Results: The knowledge about thalassemia among medical students (n597) and GPs (n171) was moderate, however, there was a significant difference; GPs greater than 30 years old had lower knowledge compared to students. Students attended blood examination had better knowledge (p 0.036). Type of anemia among students (7.9%) was different according to Mentzer index vs. Shine and Lal index; iron deficiciency anemia (5.3% % vs. 3.2%) dan β-thalassemia carrier (2.6% vs. 4.7%). Conclusions: Knowledge of thalassemia among medical students and GPs need to be enhanced, since 6-10% of Indonesian population are thalassemia carriers. Further examination is needed to confirm thalassemia carriership.